Clinical Benefit of Niraparib to TKI/mTORi-Resistance Metastatic ccRCC With BAP1-Frame Shift Mutation: Case Report and Literature Review - Lian, Bi-Jun; Zhang, Ke; Fang, Xu-Dong; Li, Feng; Dai, Zhao; Chen, Wei-Ying; Qi, Xiao-Ping (Frontiers in Oncology, 2022)
Clear cell renal cell carcinoma (ccRCC) is the most common subtype of renal cancer. The top four mutant genes affecting the occurrence and progression of ccRCC are VHL, PBRM1, BAP1, and SETD2, respectively. Tyrosine kinase/mammalian target of rapamycin inhibitors (TKI/mTORis) with or without immunotherapy are the standard and effective therapy to metastatic ccRCC. Once TKI/mTORis fail to ccRCC, there is still a lack of other effective therapies. In this study, we reported a case in which a metastatic ccRCC patient (T2aN1M1) presented resistance after a 28-month treatment by sorafenib–axitinib–everolimus (TKI-TKI-mTORi). Subsequently, a frame shift pathogenic mutation, c.799_800del (p.Q267fs) in the exon10 of BAP1 in ccRCC, was revealed by targeted sequencing. Oral administration of nilapanib (PARP inhibitor) was further given, which may provide a new therapy for TKI/mTORi-resistance metastatic ccRCC. Fortunately, a partial response has been achieved and lasted for 5 months. Since the frequency of BAP1 mutations in ccRCC patients was approximately 10%–20%, as reported previously, we also tried to explore the potential mechanisms benefitting from the nilapanib. Moreover, the literature concerning BAP1 mutation and associated cancers including ccRCC is reviewed.